Morphology of juvenile stages of Kuschelina bergi (Harold) with biological information (Coleoptera, Chrysomelidae, Alticini) - Cabrera, Nora (2016)
Fil: Cabrera, Nora. Museo de La Plata. División Entomología. La Plata, Argentina.